History of Construction Law - Arizan Putra Sitanggang; Edison Hatoguan Manurung; Dwi Purwanto (Journal of Educational Analytics, 2023)
The Construction Law is a legal regulation that plays an important role in regulating the construction industry in Indonesia. The history of Construction Law in Indonesia reflects the development of this country from the pre-independence period to the present. This article provides a brief overview of the history of Construction Law in Indonesia. This article was written with the aim that the author can understand the development of construction laws in Indonesia. And this article was written using the method of collecting data and information from various online media and existing books.